Maria Firmina dos Reis: a trajetória intelectual de uma escritora afrodescendente no Brasil oitocentista - Zin, Rafael Balseiro (2016)
The present study aims to carry out an investigation about the intellectual trajectory of Maranhão’s writer Maria Firmina dos Reis (1825-1917), from the analysis of bio-bibliographical records and literary fragments taken from the novel Úrsula, published in 1859; Gupeva tale, 1861-2; and the tell A escrava, 1887, with the purpose of achieving, critically, the senses that the author has assigned to the abolitionist cause in effect at that time. A venture like this, soon, allows the offset of the literary work for a social science research, more specifically, in an interdisciplinary perspective, who converses the literary studies with studies of brazilian social thought. In this direction, the literature assumes significance as a privileged object of investigation, able to cross time and offer the researcher significant clues about the political thought of the writer, the ways that group of people lived in society and not least, the way they dealt with the underlying issues of its generation